Polyimide-based modified polyolefin composite diaphragm and preparation method thereof

By applying polyimide ceramic composite coating and pore-generating agent to construct a porous structure on the lithium-ion battery separator, the problems of poor heat resistance and insufficient electrolyte wetting at high temperatures are solved, and higher battery safety is achieved and performance.

CN119481580AInactive Publication Date: 2025-02-18NINGBO CHANGYANG TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510074585.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators have poor heat resistance and insufficient electrolyte wetting at high temperatures, which pose safety hazards, especially after the battery energy density increases, which can easily cause thermal runaway from the battery.

Method used

Polyimide (PI) ceramic composite coating is used to construct the porous structure of the polyimide coating through a porogenic agent, which improves the electrolyte wetting and thermal stability of the membrane while maintaining good breathability.

Benefits of technology

It significantly improves the heat resistance of the diaphragm and the electrolyte affinity, improves the mechanical properties and pore distribution uniformity, and reduces the risk of thermal runaway from the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481580A_ABST
    Figure CN119481580A_ABST
Patent Text Reader

Abstract

The invention discloses a polyimide modified polyolefin composite diaphragm and a preparation method thereof, the composite diaphragm comprises a polyolefin diaphragm base material and a polyimide / ceramic particle composite coating with a porous structure arranged on one side or two sides of the polyolefin diaphragm base material, and a PI coating porous structure is constructed through a pore-foaming agent. By introducing PI, the heat resistance of the diaphragm is remarkably improved; by adding the ceramic particles, on one hand, the electrolyte wettability of the diaphragm can be further improved, better thermal stability and mechanical performance are expected, and more uniform pore distribution is generated. Lithium bromide is preferably used as a pore-foaming agent and is matched with a low-boiling-point solvent for use, on one hand, the solubility of the lithium bromide in a THF / methanol mixed solution is extremely high, and high porosity is obtained by taking the lithium bromide as a template; secondly, in the solvent drying process, lithium bromide can absorb moisture from air, and PAA is helped to be cured to construct a porous structure, so that the high-temperature-resistant composite diaphragm with excellent air permeability is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery separators, and in particular to a polyimide-modified polyolefin composite separator and a preparation method thereof. Background Art

[0002] Polypropylene (PP), polyethylene (PE) and composite PP / PE / PP are the main separator materials for lithium-ion batteries at present, showing excellent mechanical properties and stable chemical stability, and the manufacturing process is simple. However, this type of separator also has some disadvantages, such as poor high temperature resistance (such as PE melting point is 135 ℃, PP melting point is 165 ℃), and poor wettability to electrolyte, etc. These defects are the source of potential safety hazards. Especially at present, with the increase of battery energy density, local heating of the battery caused by battery collision, internal short circuit and other factors may eventually cause thermal runaway of the battery, causing a series of safety problems.

[0003] In order to overcome the above shortcomings, functional coating on the surface of commercial polyolefin separators is a low-cost modification method. Through coating, high-temperature resistant inorganic materials (such as boehmite, alumina, etc.) or organic heat-resistant materials (aramid (PPTA), polyvinylidene fluoride, polymethyl methacrylate, polyimide, etc.) can be introduced on the membrane surface to improve the heat resistance of polyolefin membranes and improve their electrolyte affinity. As a kind of excellent high temperature resistant material, polyimide can be applied to diaphragm modification to significantly improve the heat resistance of the diaphragm. For example, CN103296238B discloses a diaphragm containing an organic and inorganic mixture coating of polyimide, the main components of the coating are polyimide, organic binder and inorganic particles, wherein the polyimide is a fluorinated polyimide or polyetherimide with high heat resistance that can be dissolved in a low boiling point solvent, the organic binder is an expandable organic binder containing polyvinylidene fluoride-hexafluoropropylene copolymer, and the inorganic particles are aluminum oxide with a particle size of 1 nm to 2,000 nm, which is applied to a polyolefin substrate film to form a coating layer, thereby improving the heat resistance of the substrate film. However, the direct coating of the polyimide coating may affect the pore structure of the composite diaphragm, therefore, CN118198654A discloses a high heat resistance double-layer lithium battery diaphragm with a good pore structure by setting a polyimide coating on the diaphragm by electrospinning.

[0004] In view of this, the present invention provides a polyimide-modified polyolefin composite membrane and a preparation method thereof. The introduction of a polyimide (PI) ceramic composite coating enables the membrane to have excellent electrolyte wettability and thermal stability. At the same time, the porous structure of the polyimide coating is constructed by a porogen to maintain good air permeability of the membrane. Summary of the invention

[0005] The present invention discloses a polyimide-modified polyolefin composite diaphragm and a preparation method thereof. A porous structure of a polyimide (PI) coating is constructed by a porogen. In a low-boiling point solvent system, polyamic acid (PAA) is firstly synthesized by reacting dianhydride and diamine. The porogen and ceramic particles are then mixed into a PAA solution to form a PAA slurry, which is then scraped onto a polyolefin diaphragm to form a film. After the PAA film is dried, the porogen is extracted by a solvent to obtain a nanoporous PAA film. Finally, the PAA film is converted into a PI film by chemical imidization to obtain a PI-modified polyolefin composite diaphragm.

[0006] The present invention is achieved through the following technical solutions.

[0007] In one aspect, the present invention provides a polyimide-modified polyolefin composite membrane, comprising a polyolefin membrane substrate and a polyimide / ceramic particle composite coating having a porous structure disposed on one or both sides of the polyolefin membrane substrate.

[0008] The polyolefin diaphragm substrate includes any one or more of commercially available PE diaphragms, PP diaphragms, PP / PE diaphragms, and PP / PE / PP composite diaphragms.

[0009] The polyimide / ceramic particle composite coating comprises polyimide and inorganic ceramic particles; Specifically, the polyimide / ceramic particle composite coating is obtained by coating the PAA slurry on the substrate, followed by drying, washing, and imidization; The PAA slurry includes a solvent, PAA formed by the reaction of a dianhydride monomer and a diamine monomer in the solvent, ceramic particles and a porogen; The polyimide is obtained by chemical imidization of PAA; The molar ratio of the diamine monomer to the dianhydride monomer is 1:1.01-1.03; Preferably, the molar ratio of the diamine monomer to the dianhydride monomer is 1:1.02; The stoichiometric amount of the dianhydride is 1 mol % to 3 mol % more than the diamine in order to produce a high molecular weight PI.

[0010] The diamine monomer includes one or more of 4,4'-diaminodiphenyl ether (ODA) and 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA); The dianhydride monomer includes one or more of 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride (6FDA), 4,4'oxydiphthalic anhydride (OPDA), and 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA).

[0011] The solvent is a low boiling point solvent, that is, the boiling point of the solvent is lower than that of water; Preferably, the low boiling point solvent is a mixture of tetrahydrofuran (THF) and methanol, and the volume ratio of tetrahydrofuran to methanol is 4:1.

[0012] The porous structure is formed by adding a porogen into a PAA slurry, coating the PAA mixed slurry on the surface of a polyolefin diaphragm substrate to form a PAA film, and then extracting the porogen through a solvent after the PAA film is dried.

[0013] Furthermore, the pore size of the porous structure is about 1 to 200 nm.

[0014] Preferably, the amount of the porogen is 10 to 30 wt % of PAA (based on the total amount of dianhydride and diamine); If the amount of porogen is too much, the porosity will increase, but it will have an adverse effect on the mechanical strength of the film. If the amount is too little, a properly distributed pore structure cannot be obtained.

[0015] The porogen is any one or more of lithium bromide, PEG 400, and lithium chloride; Preferably, the porogen is lithium bromide.

[0016] The inorganic ceramic particles include one or more of aluminum oxide, boehmite, silicon dioxide, and titanium dioxide; The amount of the ceramic particles is 1-5 wt % of PAA (based on the total amount of dianhydride and diamine); The particle size of the ceramic particles is 1 to 100 nm; Preferably, the particle size of the ceramic particles is 10 to 50 nm.

[0017] On the other hand, the present invention provides a method for preparing a polyimide-modified polyolefin composite diaphragm, comprising the following preparation steps: Step 1, preparation of PAA slurry: Under nitrogen protection, in a reaction vessel, diamine monomer is added to the solvent under vigorous stirring. After the diamine monomer is completely dissolved, dianhydride monomer is added according to the reaction ratio, and the mixture is placed in a water bath at 0-5°C for 3-5 h under stirring. Subsequently, porogen and ceramic particles are added, and the reaction is continued for 5-7 h to obtain PAA slurry. The molar ratio of the diamine monomer to the dianhydride monomer is 1:1.01-1.03; Preferably, the molar ratio of the diamine monomer to the dianhydride monomer is 1:1.02; The diamino monomer includes one or more of 4,4'-diaminodiphenyl ether (ODA) and 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA); The dianhydride monomer includes one or more of 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride (6FDA), 4,4'oxydiphthalic anhydride (OPDA), and 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA); The solvent is a mixture of tetrahydrofuran and methanol, and the volume ratio of tetrahydrofuran to methanol is 4:1.

[0018] The porogen is any one or more of lithium bromide, PEG 400, and lithium chloride.

[0019] The amount of the porogen is 10-30 wt % of PAA (based on the total amount of dianhydride and diamine); The ceramic particles include one or more of aluminum oxide, boehmite, silicon dioxide, and titanium dioxide; The amount of the ceramic particles is 1-5 wt % of PAA (based on the total amount of dianhydride and diamine); The particle size of the ceramic particles is 1 to 100 nm; Preferably, the particle size of the ceramic particles is 10 to 50 nm.

[0020] Step 2: Preparation of polyimide / ceramic particle composite coating diaphragm: The PAA slurry obtained in step 1 is applied to the surface of the diaphragm substrate with a thickness of 2 to 5 μm. After the coating is applied and before drying, a layer of 30% mass concentration of porogen solution is lightly applied on the top surface of the coating. After coating, the film is placed to dry for 20 to 40 minutes until the coating is dry. Once the applied coating is dry, it is washed with deionized water and ethanol to remove the porogen, and then completely dried in a vacuum oven to obtain a dry PAA film. Then, the resulting composite diaphragm is placed in a pre-configured closed device, which contains a solution of pyridine and acetic anhydride in a molar ratio of 1:1. After heating, the corresponding vapor is formed, which is used to imidize the polyamic acid coating for 6 to 12 hours.

[0021] Step 3, post-processing: The obtained polyimide / ceramic particle composite coating diaphragm was washed with isopropanol for 1 to 3 times to remove trace residual porogen to obtain the final polyimide-modified polyolefin composite diaphragm, and the obtained lithium battery diaphragm was placed in a 90°C oven and baked for 12 h to obtain a film.

[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) The introduction of polyimide can significantly improve the heat resistance of the diaphragm; (2) On the one hand, the addition of ceramic particles can further improve the electrolyte wettability of the separator; secondly, with the addition of ceramic fillers, better thermal stability and mechanical properties can be expected; in addition, the addition of ceramic particles can produce a more uniform pore distribution; (3) Lithium bromide is preferably used as a porogen. During the solvent drying process, lithium bromide can absorb moisture from the air, which can help solidify PAA to form a porous membrane. On the other hand, lithium bromide has a very high solubility in THF / methanol mixed solution. Using lithium bromide as a porogen can obtain a uniformly distributed high porosity. (4) The present invention uses a low boiling point solvent (THF / methanol mixed solvent). Compared with conventional solvents used for PAA synthesis, such as dimethylacetamide and dimethylformamide, the boiling point of the THF / methanol mixed solvent is much lower. Since the dissolved lithium bromide will spontaneously absorb moisture in the air, thereby helping to solidify PAA, the solvent needs to evaporate quickly before absorbing a large amount of H2O to form a porous coating. If a solvent with a high boiling point (higher than H2O) is used, a large amount of H2O will be adsorbed, and the solvent is not removed, which will cause PAA to precipitate into a powder form, which is not conducive to coating film formation. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the structure of a polyimide-modified polyolefin composite diaphragm.

[0024] 1——Polyolefin diaphragm substrate; 2——Polyimide / ceramic particle composite coating. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0026] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are all conventional methods in the art. Among them, PEG 400 (analytical grade, AR) was purchased from Sinopharm Chemical Reagent Company; lithium bromide (analytical grade, AR) was purchased from Sinopharm Chemical Reagent Company; lithium chloride (analytical grade, AR) was purchased from Sinopharm Chemical Reagent Company; PE diaphragm (Hefei Changyang New Energy Technology Co., Ltd., model CW20L1).

[0027] Example 1 A polyimide-modified polyolefin composite diaphragm, comprising a polyolefin diaphragm substrate and a polyimide / ceramic particle composite coating with a porous structure arranged on both sides of the polyolefin diaphragm substrate; The polyolefin diaphragm substrate is a PE diaphragm with a thickness of 20.0±2.0 μm; The porous structure is formed by adding a porogen into a PAA slurry, coating the PAA slurry on the surface of a polyolefin diaphragm substrate to form a PAA film, and extracting the porogen through a solvent after the PAA film is dried; The specific preparation steps are as follows: Step 1, preparation of PAA slurry: Under nitrogen protection, 4,4'-diaminodiphenyl ether (ODA, 0.1 mol) was added to 500 mL of a mixed solvent of tetrahydrofuran and methanol (V 四氢呋喃 :V 甲醇 =4:1), after ODA is completely dissolved, add 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride (6FDA, 0.102 mol), and continue to react in a 0-5°C water bath with stirring for 3-5 h; then, add 10% lithium bromide (6.4 g) and 2 g of silica particles with a particle size of about 15 nm, and continue to react for 5-7 h to obtain PAA slurry.

[0028] Step 2: Preparation of polyimide / ceramic particle composite coating diaphragm: The PAA slurry obtained in step 1 was applied to the surface of the diaphragm substrate by a doctor blade, and the thickness was controlled to be 3 μm. After the coating was applied and before drying, a layer of lithium bromide solution with a mass concentration of 30% was lightly applied on the top surface of the coating. After coating, the film was left to dry for 30 minutes until the coating was dry. After the coating was dry, a mixed solution of deionized water and ethanol (V 无离子水 :V 乙醇 =1:1) to remove LiBr and create pores, and then completely dried in a vacuum oven to obtain a dry PAA coating.

[0029] Finally, the obtained composite diaphragm is placed in a pre-configured closed device, in which is a solution of pyridine and acetic anhydride in a molar ratio of 1:1. After heating, the corresponding vapor is formed, which is used to imidize the polyamic acid coating for 6 to 12 hours.

[0030] Step 3, post-processing: The obtained polyimide / ceramic particle composite coating membrane was washed with isopropanol for 1 to 3 times to remove the trace residual LiBr to obtain the final polyimide-modified polyolefin composite membrane, and the obtained membrane was placed in an oven at 90°C and baked for 12 h to obtain a film.

[0031] Example 2 The amount of lithium bromide in step 1 of Example 1 was adjusted to 20%, i.e., 12.8 g, and the remaining steps remained unchanged.

[0032] Example 3 The amount of lithium bromide in step 1 of Example 1 was adjusted to 30%, i.e., 19.2 g, and the remaining steps remained unchanged.

[0033] Example 4 The porogen in step 1 of Example 2 was replaced with lithium chloride, and the remaining steps remained unchanged.

[0034] Example 5 The porogen in step 1 of Example 2 was replaced with PEG 400, and the remaining steps remained unchanged.

[0035] Example 6 The amount of silicon dioxide in step 1 of Example 2 was adjusted to 0.7 g, and the other steps remained unchanged.

[0036] Example 7 The amount of silicon dioxide in step 1 of Example 2 was adjusted to 3.2 g, and the other steps remained unchanged.

[0037] Comparative Example 1 The amount of silicon dioxide in step 1 of Example 2 was adjusted to 0, that is, no ceramic particles were added, and the other steps remained unchanged.

[0038] Comparative Example 2 The solvent in step 1 of Example 2 was adjusted to dimethylformamide, and the remaining steps remained unchanged.

[0039] Comparative Example 3 The solvent in step 1 of Example 2 was adjusted to dimethylacetamide, and the remaining steps remained unchanged.

[0040] Comparative Example 4 As in the preparation steps of Example 2, the amount of the porogen used is 0, that is, no porogen is added.

[0041] Comparative Example 5 The preparation steps are the same as those in Example 2, except that the step of "after coating is completed but before the coating is dried, lightly coating the top surface of the coating with a layer of lithium bromide solution having a mass concentration of 30%" in step 2 is omitted, and the other operations remain unchanged.

[0042] Comparative Example 6 The preparation steps were the same as those in Comparative Example 5, except that the porogen was changed from lithium bromide to PEG 400, and the other steps remained unchanged.

[0043] Comparative Example 7 The conventional PE separator used in Example 1 was not subjected to any coating treatment.

[0044] The performance of the composite diaphragms prepared in Examples 1-7 and Comparative Examples 1-7 was tested in the following manner, and the data results are shown in Table 1: (1) Air permeability test: The test was conducted according to the air permeability test method in the national standard GB / T-36363-2018. The air permeability results were expressed by the Gurley value. The smaller the Gurley value, the shorter the time for gas to pass through, and the better the air permeability of the diaphragm. Based on the Gurley standard value of the PE diaphragm being 55±25, it is considered qualified if it is within this range; (2) Heat resistance test: The heat resistance of the diaphragm is characterized by the heat shrinkage rate. The test is carried out according to the test method for heat shrinkage rate in the national standard "GB / T-36363-2018". The instrument uses a blast oven. It is generally considered that the heat shrinkage rate (%) of 130℃ / 1h MD≤3, TD≤2 is qualified; (3) Tensile strength test: Test according to the tensile strength test method in the national standard "GB / T-36363-2018"; (4) Liquid absorption rate test: A 1 mol / L lithium hexafluorophosphate solution in dimethyl carbonate and ethyl methyl carbonate were mixed in a volume ratio of 1:1 to prepare an electrolyte. The composite diaphragm sample was then immersed in the electrolyte for 12 h. After completion, the excess electrolyte on the surface was wiped off and the liquid absorption rate was calculated. (5) Ionic conductivity (mS / cm) test: The bulk resistance was tested by using the electrochemical impedance spectroscopy (EIS) mode of a VMP3B-10 electrochemical workstation (Bio-Logic Science Instruments) in the assembly mode of steel sheet / diaphragm / steel sheet, where the disturbance voltage amplitude was 5 mV and the frequency was 10 mHz to 1 MHz; the relationship between bulk resistance and ionic conductivity is: ionic conductivity = diaphragm thickness / (diaphragm resistance*contact area between diaphragm and electrode)*10 -2 , where the unit of diaphragm thickness is mm, the unit of diaphragm resistance is Ω, and the unit of contact area between diaphragm and electrode is m2.

[0045] Table 1 Summary of performance test data of composite diaphragms prepared in Examples 1-7 and Comparative Examples 1-7

[0046] In Examples 1 to 3, the amount of lithium bromide was regulated. From the data comparison in Table 1, it can be seen that when the amount of lithium bromide is 20% to 30% based on the total amount of dianhydride and diamine, the film-forming performance is more excellent, and the Gurley value is low, which is similar to that of the PE bare film, indicating that the porosity of the coating is high and the pore structure is well distributed. In addition, due to the introduction of the polyimide and ceramic composite coating, the heat resistance of the composite diaphragm is significantly improved, and the thermal shrinkage rate at 130°C / 1h is significantly lower than that of the PE bare film (Comparative Example 7). At the same time, the tensile strength and liquid absorption rate are improved.

[0047] Comparison of Example 2 with Examples 4 and 5 shows that the composite diaphragm based on lithium bromide porogen has better performance, which is mainly due to its use in combination with low boiling point solvents. On the one hand, lithium bromide has extremely high solubility in THF / methanol mixed solution, and high porosity can be obtained with lithium bromide as a template; secondly, during the solvent drying process, lithium bromide can absorb moisture from the air, so before absorbing a large amount of H2O, the solvent needs to evaporate quickly to help solidify PAA to build a porous structure. However, lithium chloride has stronger ionic bond force and low solubility in THF / methanol mixed solution, so it has worse miscibility with PAA slurry, resulting in poor porosity during later elution, uneven pore distribution, and large differences in pore size, resulting in poor mechanical properties of the formed film. In Example 5, PEG400 is used as a porogen. Since PEG400 has a large molecular weight and contains a large amount of -OH in its structure, and there are a large number of -H bonds in the polyimide system, with the addition of polyethylene glycol, there are a large number of hydrogen bonds and cross-linking points in the entire system, which can enhance the tensile strength of the system to a certain extent. However, it will also cause PEG400 to be difficult to elute and remain in the polyimide system, resulting in a poor pore structure and poor air permeability of the film.

[0048] By comparing the data of Example 2, Example 6, 7 and Comparative Example 1, it can be found that the addition of ceramic particles can further improve the electrolyte wettability of the diaphragm; secondly, after adding ceramic fillers, better thermal stability and mechanical properties can be obtained; and with the addition of SiO2, the pore distribution can be made more uniform. This may be because some particles enter the pores formed by the porogen as part of the skeleton, play a supporting role, and can preserve the soaked electrolyte and thus improve the liquid absorption rate of the diaphragm. In other words, the addition of appropriate ceramic particles can improve the pore distribution, increase the contact area of ​​the diaphragm, and effectively improve the liquid absorption rate of the diaphragm; however, if too many particles are added, the pores may be blocked, which is not conducive to the air permeability of the diaphragm, and poor dispersion in the polyimide system leads to poor tensile strength.

[0049] It can be seen from the data of Comparative Examples 2 and 3 that the coating cannot form a film when lithium bromide is used as a porogen and conventional solvents such as dimethylacetamide and dimethylformamide are used. This is mainly because dimethylacetamide and dimethylformamide are solvents with high boiling points (higher than H2O), and a large amount of H2O is adsorbed without removing the solvent, causing PAA to precipitate into a powder form, making it impossible for the coating to form a porous film. In addition, the presence of the powder destroys the original pore structure of the diaphragm substrate and affects its air permeability.

[0050] Comparative Example 4 does not add a porogen. Compared with Example 2, the polyimide / ceramic composite coating has no pore structure and the coating film appears transparent. Due to the absence of a pore structure, the composite diaphragm has high tensile strength, low thermal shrinkage, and excellent heat resistance. However, the air permeability is extremely poor, and the liquid absorption rate and ionic conductivity are poor.

[0051] Comparative Examples 5 and 6 are based on the implementation steps of lithium bromide porogen and PEG400 porogen, respectively, omitting the sealing step of "after coating in step 2 and before the coating is dried, lightly applying a layer of porogen solution with a mass concentration of 30% on the top surface of the coating" to investigate its effect on the final film-forming performance. It was found that the air permeability of the composite membrane deteriorated, indicating that the introduction of porogen on the surface of the film in this step contributes to the formation of its surface pore structure, thereby promoting uniform distribution of film-forming pores.

Claims

1. A polyimide-modified polyolefin composite diaphragm, comprising a polyolefin diaphragm substrate, and a porous polyimide / ceramic particle composite coating disposed on one or both sides of the polyolefin diaphragm substrate, characterized in that: The polyimide / ceramic particle composite coating is obtained by coating a polyamic acid slurry on a substrate, followed by drying, extraction, and imidization; the polyamic acid slurry includes a solvent, polyamic acid formed by the reaction of a dianhydride monomer and a diamine monomer in the solvent, ceramic particles, and a porogen; The porogen includes lithium bromide; The amount of the ceramic particles is 1-5 wt% of the total amount of dianhydride and diamine; The amount of the porogen is 10-30 wt% of the total amount of dianhydride and diamine; The solvent in the polyamic acid slurry is a solvent having a boiling point lower than that of water.

2. A polyimide-modified polyolefin composite diaphragm according to claim 1, characterized in that: The dianhydride monomer includes one or more of 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride, 4,4'oxydiphthalic anhydride, and 3,3',4,4'-benzophenonetetracarboxylic dianhydride; the diamine monomer includes one or more of 4,4'-diaminodiphenyl ether and 2-(4-aminophenyl)-5-aminobenzimidazole; the polyolefin diaphragm substrate includes any one or more of commercially available PE diaphragms, PP diaphragms, PP / PE diaphragms, and PP / PE / PP composite diaphragms.

3. A polyimide-modified polyolefin composite diaphragm according to claim 2, characterized in that: The pore size distribution of the porous structure of the polyimide / ceramic particle composite coating is 1 to 200 nm. The porous structure is formed by adding a porogen into a polyamic acid slurry, coating the polyamic acid slurry on the surface of a polyolefin diaphragm substrate to form a polyamic acid film, and then extracting the porogen through a solvent after the polyamic acid film is dried.

4. A polyimide-modified polyolefin composite diaphragm according to claim 3, characterized in that: The ceramic particles include one or more of aluminum oxide, boehmite, silicon dioxide, and titanium dioxide; and the particle size of the ceramic particles is 1 to 100 nm.

5. The polyimide-modified polyolefin composite diaphragm according to claim 4, characterized in that: The solvent having a boiling point lower than that of water is a mixture of tetrahydrofuran and methanol, and the volume ratio of tetrahydrofuran to methanol is 4:1 by volume.

6. A method for preparing a polyimide-modified polyolefin composite diaphragm according to any one of claims 1 to 5, characterized in that: The method comprises the following preparation steps: Step 1, preparation of polyamic acid slurry: under nitrogen protection, add diamine monomer to solvent in a reaction container under vigorous stirring, after the diamine monomer is completely dissolved, add dianhydride monomer according to the reaction ratio, and continue to react under stirring in a water bath at 0-5°C for 3-5 hours; then, add porogen and ceramic particles, and continue to react for 5-7 hours to obtain polyamic acid mixed slurry; Step 2, preparation of polyimide / ceramic particle composite coating diaphragm: apply the polyamic acid slurry obtained in step 1 to the surface of the diaphragm substrate; after the coating is applied but before drying, lightly apply a layer of 30% mass concentration of porogen solution on the top surface of the coating, after coating, place the film to dry for 20 to 40 minutes until the coating is dry; once the applied coating is dry, wash it with a mixed solution of deionized water and ethanol to remove the porogen, and then dry it in a vacuum oven to obtain a dry polyamic acid film; finally, perform imidization treatment on the polyamic acid coating of the obtained composite diaphragm for 6 to 12 hours.

7. The method for preparing a polyimide-modified polyolefin composite diaphragm according to claim 6, characterized in that: The method further includes a post-processing step, namely, washing the polyimide / ceramic particle composite coating diaphragm obtained in step 2 with isopropanol for 1 to 3 times to remove trace residual porogens to obtain a final polyimide-modified polyolefin composite diaphragm, and placing the obtained diaphragm in an oven at 90° C. and baking for 12 hours to obtain a film.

8. The method for preparing a polyimide-modified polyolefin composite diaphragm according to claim 7, characterized in that: The molar ratio of the diamine monomer to the dianhydride monomer in the step 1 is 1:1.01-1.

03.

9. The method for preparing a polyimide-modified polyolefin composite diaphragm according to claim 8, characterized in that: The imidization treatment in step 2 is to place the obtained polyimide / ceramic particle composite diaphragm in a pre-configured closed device, in which there is a solution of pyridine and acetic anhydride configured in a molar ratio of 1:1, which is heated to form corresponding vapor for imidization treatment of the polyamic acid coating.

10. The method for preparing a polyimide-modified polyolefin composite diaphragm according to claim 9, characterized in that: The thickness of the polyimide / ceramic particle coating of the composite diaphragm is 2-5 μm; the amount of the ceramic particles is 1-5 wt% of the total amount of the dianhydride and the diamine, and the amount of the porogen is 10-30 wt% of the total amount of the dianhydride and the diamine.

Citation Information

Patent Citations

  • Including membranes coated with organic and inorganic mixtures containing polyimide.

    CN103296238B

  • Polyimide porous membrane, preparation method thereof and lithium ion battery

    CN101645497A

  • Preparation method for polyimide modified composite battery membrane and product prepared therethrough

    CN108172742A

  • A polyimide lithium battery diaphragm, a preparation method thereof, and a lithium battery comprising the diaphragm

    CN109119572A

  • Porous polyimide film, preparation method thereof and lithium ion battery

    CN110828750A